High energy radiation induced degradation of reactive yellow 145 dye: A mechanistic study. (December 2020) - Muneer, Majid; Kanjal, Muhammad Imran; Saeed, Muhammad; Javed, Tariq; Haq, Atta Ul; Ud Den, Nighat Zia; Jamal, Muhammad Asghar; Ali, Saddaqat; Iqbal, Munawar
Abstract: Gamma and UV radiation alone and in the presence of oxidant (H2 O2 ) were employed for the degradation of reactive yellow 145 dye. The observed degradation was 82.73 and 77.93% under UV radiation, while 100 and 94.84% using gamma ray treatment for 50 and 100 mg/L drug initial concentrations along with H2 O2, respectively. The reduction in COD was noted as 73 and 60% for 50 and 100 mg/L dye initial concentrations using gamma/H2 O2 combined process, respectively. The pH was reduced significantly when the samples were treated with gamma/H2 O2 . The removal efficiency (G-value), dose constant (k), D0.50, D0.90 and D0.99 of gamma-ray treated samples were also evaluated. The cytotoxicity and mutagenicity were measured, which reduced significantly in response of radiation treatment. The 44.45 and 55.56% decrease in cytotoxicity was shown by the Allium cepa, whereas 77.45 and 80.41% in case of hemolytic while 83.75 and 88.65% reduction in cytotoxicity was noted by the shrimp assay using UV/H2 O2 and gamma/H2 O2 treatments, respectively. The mutagenicity of dye solutions was reduced to 78.25 and 83.13% (in case of TA98), while 82.53 and 85.32% (in case of TA100) using UV/H2 O2 and gamma/H2 O2 processes, respectively. Results suggested that AOP can efficiently be used to degrade and detoxify the textile wastewater. Highlights: High energy irradiation induced degradation of Yellow 145 dye was evaluated. Kinetics, G-value, dose constants were evaluated as a function radiation absorbed dose. Effect of dose on degradation, water quality and toxicity reduction was studied. Gamma/H2 O2 reduced toxicity of dyes along with improvement in water quality. High energy radiation induced degradation of dye was promising.